2023
DOI: 10.1371/journal.pone.0287811
|View full text |Cite
|
Sign up to set email alerts
|

Readmission prediction after colorectal cancer surgery: A derivation and validation study

Abstract: Background Unplanned readmissions after colorectal cancer (CRC) surgery are common, expensive, and result from failure to progress in postoperative recovery. The context of their preventability and extent of predictability remains undefined. This study aimed to define the 30-day unplanned readmission (UR) rate after CRC surgery, identify risk factors, and develop a prediction model with external validation. Methods Consecutive patients who underwent CRC surgery between 2012 and 2017 at Christchurch Hospital … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 37 publications
(58 reference statements)
0
3
0
Order By: Relevance
“…Early postoperative hospital readmissions are also common, costly, and associated with increased mortality rates. [11][12][13] Research has shown that up to 27% of cancer patients discharged from hospitals are readmitted, 14 contributing to the healthcare burden in morbidity and mortality. 11 During the COVID-19 pandemic, most surgical procedures were performed for emergency or oncologic reasons to the detriment of the remaining elective procedures for benign conditions.…”
Section: Original Investigationmentioning
confidence: 99%
See 2 more Smart Citations
“…Early postoperative hospital readmissions are also common, costly, and associated with increased mortality rates. [11][12][13] Research has shown that up to 27% of cancer patients discharged from hospitals are readmitted, 14 contributing to the healthcare burden in morbidity and mortality. 11 During the COVID-19 pandemic, most surgical procedures were performed for emergency or oncologic reasons to the detriment of the remaining elective procedures for benign conditions.…”
Section: Original Investigationmentioning
confidence: 99%
“…[11][12][13] Research has shown that up to 27% of cancer patients discharged from hospitals are readmitted, 14 contributing to the healthcare burden in morbidity and mortality. 11 During the COVID-19 pandemic, most surgical procedures were performed for emergency or oncologic reasons to the detriment of the remaining elective procedures for benign conditions. 15 Ileostomy and colostomy are sequelae of oncologic or emergency colorectal surgery.…”
Section: Original Investigationmentioning
confidence: 99%
See 1 more Smart Citation